Tinkering at the Limits: agricultural shows, small-scale producers and ecological connections. Issue 2 (3rd April 2017) - Turner, Bethaney; Henryks, Joanna; Main, George; Wehner, Kirsten
ABSTRACT: Agricultural shows in Australia are typically depicted as celebrations of colonisation and scientific and technical modernisation in food production. The historical focus of shows is on competition to maximise perceived quality and yield of goods, from wheat to cattle. Through these frameworks, shows are often understood as supporting industrial-scale agricultural practices that promote an ecologically-blind approach to food production. However, we suggest that competitions in contemporary agricultural shows play a role in contesting the limits of such anthropocentric thinking. We focus on a hitherto unexplored aspect of agricultural shows: small-scale growers who exhibit produce in their annual local show competitions. Through a case study drawing on interviews with exhibitors and judges, combined with participant observation at the 2012 Royal Canberra Show, we highlight the complex relationships between people, place and more-than-humans in this unique cultural site. In so doing, we suggest that exhibiting in the show can intensify urban and peri-urban small-scale producer engagement in practices of 'tinkering'. This facilitates embodied encounters with the limits of both human mastery and those of the materiality of non-humans involved in food production. Through the ongoing, adaptive processes of tinkering encouraged by such competitions, we suggest that exhibiting in agricultural shows can support the growth of ecologically informed, place-based understandings of the food system and challenge binaries of the rural/city divide.